Gut Microbiota Composition and Metabolites as the new Determinants of Cardiovascular Pathology Development - O. M. Drapkina; A. N. Kaburova (Столичная издательская компания, 2020)
Chronic noncommunicable diseases represent one of the key medical problems of the XXI century. In this group cardiovascular diseases (CVD) are known to be the leading cause of death which pathogenesis still has the potential to be more profoundly revealed in order to discover its yet unknown but essential factors. The last decades are marked by the active investigation into the gut bacterial role in the initiation and progression of CVD. The result of this investigation has been the appreciation of microbiome as the potentially new cardiovascular risk factor. The development of sequencing techniques, together with bioinformatics analysis allowed the scientists to intensively broaden the understanding of the gut microbiota composition and functions of its metabolites in maintaining the health and the development of atherosclerosis, arterial hypertension and heart failure. The interaction between macro- and microorganisms is mediated through the variety of pathways, among which the key players are thought to be trimethylamine-N-oxide (TMAO), short chain fatty acids (SCFA) and secondary bile acids. TMAO is known due to its role in atherosclerosis development and the increase in major cardiovascular events. In the majority of research SCFA and secondary bile acids have demonstrated protective role in CVD. The great attention is being paid to the role of lipopolysaccharide of gram negative bacteria in the development of systemic low-grade inflammation due to the metabolic endotoxemia which contributes to the progression of CVD. The described interactions draw attention to the opportunity to influence on the certain mechanisms of CVD pathogenesis through the modulation of microbiota composition and function. The review is aimed at highlighting the current data about the mechanisms by which the gut microbiota and its metabolites may increase cardiovascular risk and events rate as well as discussing the existing results and future perspective of bacterial systemic effects modulation.